Mind Mapping as a Strategy to Improve Idea Organization in Writing among Grade 10 Students at SMK Telkom 2 Medan - Sherine; Apryllia Cendrasa; Lilis Handayani Napitupulu; Evi Novalin Bako (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study investigated the effectiveness of mind mapping as a pre-writing strategy to improve idea organization in writing among Grade 10 students at SMK Telkom 2 Medan. The study employed a quasi-experimental design using a one-group pretest–posttest model involving 27 students. Data were collected through writing tests and a student perception questionnaire. The writing tests were assessed using an analytic rubric focusing on idea organization. The results showed that the mean score increased from 64.33 in the pretest to 77.93 in the posttest, indicating an improvement of 13.60 points. A paired-sample t-test revealed that the difference was statistically significant (t = 18.27, p < .001). The effect size analysis (Cohen’s d = 1.42) indicated a large effect of the treatment. The effect size analysis also indicated a strong impact of the treatment. Furthermore, the questionnaire results showed that most students had positive perceptions of mind mapping, reporting that it helped them generate ideas, organize their thoughts logically, and increase their confidence in writing. These findings suggest that mind mapping is an effective pre-writing strategy for enhancing students’ idea organization in EFL writing. Therefore, integrating mind mapping into writing instruction is recommended to support students in planning and structuring their ideas before drafting.Keywords: EFL students, idea organization, mind mapping, pre-writing strategy, writing skill